Research of the total spectral density of signals in the LTE up-link - A. A. Novikova; V. M. Kozel; K. A. Kavaliou (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2020)
This article is devoted to the analysis of the total spectral radiation density of LTE subscriber terminals. The LTE network uses orthogonal frequency division multiple access (OFDMA) technology for downlink communications, and multiple access technology with single-carrier frequency division multiple access (SC-FDMA) for uplink communications. In a downlink, the occupied radio frequency band is determined by the number of resource blocks and the size of the step of placement of subcarrier oscillations in the frequency domain. Features of the technologies used for organizing multiple access in LTE networks determine the nature of the spectral density of the total radio signal. Thus, in a downlink, the spectral density approaches uniformity, since the power distribution in the spectral region does not depend on the number and location of resource blocks allocated to the subscriber, and also does not depend on the territorial location of the subscriber itself. For an uplink, the determination of spectral density characteristics is not so unambiguous, since they depend on a number of factors (traffic parameters, the nature of radio conditions, etc.). Тo conduct a detailed analysis of the spectral radiation density of a set of LTE subscriber terminals, a scheme of the measuring unit was developed and experimental studies of the spectral density were conducted on the basis of the BSUIR research laboratory. The article presents spectrograms of a set of signals in the uplink of the LTE communication network, obtained for different time intervals and different places of observation. The conclusion is made about the possibility of using an equivalent uniform spectral density to describe interference effects from groupings of subscriber terminals of LTE communication networks.